FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WANITA USIA SUBUR (WUS) MELAKUKAN DETEKSI DINI KANKER SERVIKS MELALUI TES IVA - Ade Yusnida Harahap; Gamya Tri Utami; Riri " Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractEasily detectable cancer is cervical cancer, but based on the fact that more than 50% of women diagnosed with cancer is never early detected. This study aimed to determine factors related to the behavior of Woman of Childbearing Age (WCBA) early detection of cervical cancer through test VIA. The research used descriptive correlation design with cross sectional approach. The sample are 91 respondent usedincidental sampling with selected base inclusion criteria.Instrument used in the study was  questionnaires to measure variables that attitude, motivation, knowledge, husband support, the support of health professionals as well as cadres support. The analysis used are univariate and bivariate with chi square test. The results showed that the factor of knowledge (p value 0,000), husband support (p value 0,015), the support of health workers (p value 0,02) and support cadre (p value 0,034)  can be concluded there is a relationship with WUS behavior early detection of cervical cancer through VIA test. The results of this study need to be done on the implementation of health promotion increase VIA test. With VIA test will be detected cervical cancer as early, so the death amount cervical cancer can be prevented Keywords: Cervical cancer, early detection, VIA test, WCBA